Producing Quality Peanut Seed - Elmo B. Whitty (EDIS, 2002)
This document is SS-AGR-187, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date November 2002.